Jejunal perforation secondary to trichobezoar (Rapunzel syndrome): a rare presentation - Saroj, Jitendra Kumar; Ahmad, Arshad; Kumar, Pankaj; Verma, Sandeep (International Surgery Journal, 2019)
Trichobezoar is a rare disorder. It usually occurs in young and adolescent females associated with some psychiatric illness. Trichobezoar usually accumulate in the GI tract and most commonly in stomach but it can migrate through the pylorus into the jejunum, ileum and colon. Once the bezoars extends from the stomach into the jejunum or further on, it is referred to as “Rapunzel syndrome”. Though initially asymptomatic but over a period of time it may cause gastric mucosal erosion, ulceration, and perforation of the stomach or the small intestine. If unrecognized, tichobezoar may present with intussusceptions, obstructive jaundice, protein-losing enteropathy, pancreatitis and even death. Small trichobezoar may be extracted by endoscopic fragmentation but bezoars like Rapunzel Syndrome, on the other hand, need open surgical removal. Counseling by a psychiatrist is an important part of management to prevent recurrence.